Audio 3D e o corpo plugado: uma análise sobre imersão sonora na série Stranger Things - Costa, Bruna Rafaella Almeida da (2019)
The work presented here is about a study of 3D audio technology within the context of cyberspace, a type of sound experience that provides immersion of the user. Of all the possibilities and field of study, a serial narrative on the web was chosen for the investigation, particularly the Stranger Things Series. It consists of, from a Case Study to understand how this immersion becomes expressive possibility within the serial narrative. Concepts about convergence, narrative and binaural audio were approached to better understand this field of research. We worked with the cultural transformation from the emergence of the internet and through this way realize how Virtual Reality (VR) influences the human body based on the studies of Santaella (2003). The narrative was approached within its structure with emphasis on Todorov's studies (2016) and the elements that composes sound in an audiovisual product through Chion (2011) and Rodriguez (2006). There was a content analysis and analysis of a series of strange things, from a site in the series Stranger Things, which highlights: Sound with a Transmedia and Sound as a Narrative of Body Extension. thus demonstrating a reconfiguration of serial products in cyberspace through sound immersion.